Table tennis after the introduction of the 40mm-ball and the 11-point format - Zhang, H.; Hohmann, A. (Journal of Sports Sciences, 2006)
The differences between a 40mm- and a 38mm-ball in physics as well as between an11- and a 21-point game format in theory have been extensively studied since the ITTF has reformed table tennis rules. In contrast, possible differences in playing techniques and game tactics have not been evaluated yet.